High‐throughput behavioral phenotyping of tiny arthropods: Chemosensory traits in a mesostigmatic hematophagous mite. Issue 1 (2nd September 2022) - Masier, Stefano; Taudière, Adrien; Roy, Laurent J. M.; Carrasco, David; Barnagaud, Jean‐Yves; Planchon, Camille; Soulié, Anne‐Sophie; Sleeckx, Nathalie; Roy, Lise
Abstract: Pest management using attractive and/or repellent semiochemicals is a key alternative to synthetic insecticides. Its implementation requires a good understanding of the intra‐ and interspecific chemical interactions of arthropod pests, their interactions with their abiotic environment, as well as their evolutionary dynamics. Although mites include many pest species and biocontrol agents of economic importance in agriculture, their chemical ecology is largely understudied compared to insects. We developed a high‐throughput ethomics system to analyze these small arthropods and conducted a study on Dermanyssus gallinae, a problematic poultry parasite in the egg industry. Our purpose was to elucidate the role played by host‐derived odorants (synthetic kairomone) and conspecific odorants (mite body odors) in D. gallinae . After validating our nanocomputer controlled olfactometric system with volatile semiochemicals of known biological activity, we characterized response traits to kairomonal and/or pheromonal volatile blends in mites from different populations. We were able to accurately characterize the repulsion or attraction behaviors in >1000 individual specimens in a standardized way. Our results confirm the presence of a volatile aggregation pheromone emitted by D. gallinae and bring new elements to the effect of odor source presentation. Our results also confirm the attractive effect on Dermanyssus gallinae of a blend of volatile compounds contained in hen odor, while highlighting a repellent effect at high concentration. Significant interindividual and interpopulation variation was noted particularly in responses to synthetic kairomone. This information lays a valuable foundation for further exploring the emergence risk of resistance to semiochemicals. Abstract : We validated a new high‐throughput system based on nanocomputers connected to cameras automatically tracking movements of single mites. Our results confirm the existence of a volatile pheromone deposited by D. gallinae and attractive to conspecifics. They also show that a mixture of volatile compounds contained in the hen odor is attractive at low concentrations and repulsive at higher concentrations. RESEARCH HIGHLIGHTS: Through a new high‐throughput system based on nanocomputers connected to cameras automatically tracking movements, we highlight behavioral responses of a hematophagous mite species to kairomones and pheromones.